Exploring the Mechanisms of Zhenbao Pills in the Treatment of Stroke through Network Pharmacology Combined with Mendelian Randomization - Yanhong Liu; Yunqi Hua; Xiaoe Jia (Journal of Bio-X Research)
Background: Stroke causes substantial death and disability worldwide, challenging healthcare systems and impacting patients' lives. Research on stroke biomarkers can aid in the development of targeted therapies, while Zhenbao Pills (ZBP) from traditional Chinese medicine may enhance recovery from neurological disorders. Further investigations into the mechanisms of ZBP are crucial for better stroke management. Methods: This research accessed databases to pinpoint the core components and identify the targets of ZBP and stroke. “Drug–component–target” networks were established, followed by enrichment analysis of identified targets. We also used Mendelian randomization (MR) to assess causal relationships between feature genes and stroke incidence, for which colocalization was employed for validation. Furthermore, molecular docking and Gene Expression Omnibus (GEO) datasets were used for preliminary confirmation. Results: This study identified 14 core components and 105 stroke-related targets for ZBP. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses revealed that these targets are involved mainly in oxidative stress processes, lipid metabolism, and the PI3K–Akt signaling pathway. Correlation with stroke risk was determined through MR analysis, which revealed that the VEGFA and ARG1 genes were negatively correlated with stroke risk and GATM was positively correlated. Additionally, the stable interactions of molecular docking and differential expression of key genes support their potential therapeutic relevance. Conclusion: Stroke may be mitigated through essential constituents of ZBP (e.g., luteolin, quercetin, and isorhamnetin) that target pivotal genes (e.g., VEGFA, ARG1, and GATM), including characteristic genes, and the modulation of oxidative stress and inflammation-related pathways. These discoveries hold important implications for clinical practice and future research endeavors.